Comparison of Homogeneous and Heterogeneous Catalysts for Glucose‐to‐Fructose Isomerization in Aqueous Media. Issue 12 (17th September 2013) - Choudhary, Vinit; Pinar, Ana B.; Lobo, Raul F.; Vlachos, Dionisios G.; Sandler, Stanley I.
Abstract Herein, the first comparison of the mechanisms of glucose‐to‐fructose isomerization in aqueous media enabled by homogeneous (CrCl3 and AlCl3) and heterogeneous catalysts (Sn‐beta) by using isotopic‐labeling studies is reported. A pronounced kinetic isotope effect (KIE) was observed if the deuterium label was at the C2 position, thus suggesting that a hydrogen shift from the C2 to C1 positions was the rate‐limiting step with the three catalysts. 13C and 1H NMR spectroscopic investigations confirmed that an intra‐hydride‐transfer reaction pathway was the predominant reaction channel for all three catalysts in aqueous media. Furthermore, the deuterium atom in the labeled glucose could be mapped onto hydroxymethylfurfural and formic acid through reactions that followed the isomerization step in the presence of Brønsted acids. In all three catalysts, the active site appeared to be a bifunctional Lewis‐acidic/Brønsted‐basic site, based on a speciation model and first‐principles calculations. For the first time, a mechanistic similarities between the homogeneous and heterogeneous catalysis of aldose‐to‐ketose isomerization is established and it is suggested that learning from homogeneous catalysis could assist in the development of improved heterogeneous catalysts.